BATU SPLIT DAN CUTTING BOR UNTUK MATERIAL STEMMING DALAM KEGIATAN PEMBERAIAN BATUAN DENGAN PELEDAKAN - Romla Noor Hakim; Nurhakim Nurhakim; Kartini Kartini; Akhmad Ridha (Universitas Lambung Mangkurat, 2016)
At mining industry usually use blasting method to breaking hard and compact rock. Blasting operation using two types of stemming material such drill cutting and crushed rock or composite of both. Stemming is column at the top of blast hole that filled by its. Length of stemming column and types of stemming materials can influence the result of blasting fragmentation. Longer stemming will produce a boulder while shorter stemming will produce fly rock and the fragment size is too small. Stemming material too soft can cause the blast energy distribution not separated well so the blasting operation achievement is not optimum.This research observed and evaluated the blasting fragment size, boulder, and blasting recovery that occur from mining blasting activity used two types stemming material such drill cutting and crushed stone.The result indicated use of drill cutting material is not strong enough to withstand the blast energy towards to the top of blasting hole then produce fly rock and 26.6 % boulder. Crushed stone material gives the best result for 10.09% boulder and 93% blasting recovery but need more expense for it. The improvement using double deck method with combine stemming material is better and gives the optimum blasting with 8.8% boulder and 91% blasting recovery.